Countercyclical prudential tools in an estimated DSGE model - Serafin Frache; Javier Garcia-Cicco; Jorge Ponce (Latin American Journal of Central Banking (LAJCB), 2023)
We developed a dynamic stochastic general equilibrium (DSGE) model for a small, open economy with a banking sector and endogenous default to assess two macroprudential tools: countercyclical capital buffers (CCB) and dynamic provisions (DP). The model is estimated with data for Uruguay, where dynamic provisioning has existed since the early 2000s. Both tools force banks to build buffers, but DP seem to outperform the CCB in smoothing the cycle. We also find that the source of the shock affecting the financial system matters in assessing the relative performance of both tools. Given a positive external shock, the credit-to-GDP ratio decreases, which should discourage its use as an indicator variable to activate countercyclical regulation.
Keywords: G21; G28; 330; (Countercyclical or dynamic) loan loss provision; Banking regulation; Basel III; Countercyclical capital buffer; DSGE; Endogenous default; Minimum capital requirement; Reserve requirement; Uruguay